2021
DOI: 10.1038/s41598-021-00415-2
|View full text |Cite
|
Sign up to set email alerts
|

HIV-2 Vpx neutralizes host restriction factor SAMHD1 to promote viral pathogenesis

Abstract: SAMHD1, a human host factor found in myeloid cells which restricts HIV-1 replication. It depletes the dNTPs pool for viral cDNA syntheses, thus preventing the viral replication in the cells. The viral accessory protein, Vpx, exists only in SIVmac/HIV-2 particles. Vpx in SIVmac can induce proteosomal degradation of SAMHD1, which then leads to a decrease in the cytoplasmic dNTP pool. The protein–protein interaction between Vpx and SAMHD1 and its consequences are still unclear. Methods: In this study, we cloned, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…It was previously shown that HIV-1 Vpr can induce IL-6 production in monocyte-derived macrophages (MDMs) [54]. When we assayed for the level of cytokines in the medium of transfected cells, we found that Vpx resulted in the increase of proin ammatory cytokines (IL-6 and IL-1β), in addition to TGFβ, which is in agreement with other's ndings [55], where level of secreted IL-6 and IL-1β were signi cantly increased in SIV and HIV-2 infected cells. This nding supports the role of HIV-2 Vpx in modulating the immune system.…”
Section: Discussionsupporting
confidence: 91%
“…It was previously shown that HIV-1 Vpr can induce IL-6 production in monocyte-derived macrophages (MDMs) [54]. When we assayed for the level of cytokines in the medium of transfected cells, we found that Vpx resulted in the increase of proin ammatory cytokines (IL-6 and IL-1β), in addition to TGFβ, which is in agreement with other's ndings [55], where level of secreted IL-6 and IL-1β were signi cantly increased in SIV and HIV-2 infected cells. This nding supports the role of HIV-2 Vpx in modulating the immune system.…”
Section: Discussionsupporting
confidence: 91%
“…We note that SAMHD1 moderately inhibits HCV or JEV compared with HIV or other DNA viruses. One possibility is that these viruses evolved a partial resistance to SAMHD1 during a long evolutionary process (26). The other possibility is that some other host factors induced by type1 IFN, such as CypA, assist in the formation of HCV replicase complex or guard HIV nucleic acids from cytosolic sensors, which counters the inhibition of SAMHD1 (27).…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription is an essential step in the lentiviral lifecycle and SAMHD1 effectively inhibits RT and viral replication [ 220 ]. Vpx, encoded by HIV-2 and some lineages of SIV, counteracts the activity of SAMHD1 by targeting the restriction factor for proteasomal degradation [ 175 , 176 , 215 , 221 ]. Vpx and SIV Vpr assemble with DCAF1 (also known as VPRBP) a substrate receptor for Cullin 4 CRL (Cullin Ring ubiquitin ligase) and target SAMHD1 for degradation, allowing for productive infection to occur [ 175 , 176 , 177 ].…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%